Klippel-Trenaunay-Weber syndrome with hemimegalencephaly: report of a case - Alpay, Faruk; Kürekçi, A.Emin; Güneşli, Selçuk; Gökçay, Erdal (The Turkish Journal of Pediatrics, 1996)
A case of Klippel-Trenaunay-Weber Syndrome (KTWS) in a 2.5-year-old girl with congenital hemihypertrophy, nevus flammeus and liver hemangioma is presented. In addition, this report describes the rare association of hemimegalencephaly with KTWS.